2013
DOI: 10.2527/jas.2013-6909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying concentrations of vitamin C on performance, blood metabolites, and carcass characteristics of steers consuming a common high-sulfur (0.55% S) diet

Abstract: The objective of this study was to examine the effects of vitamin C (VC) supplementation for an average of 102 d before harvest on finishing performance and blood metabolites of steers receiving a 40% dry distillers grains plus solubles diet (0.55% S). Yearling, Angus-cross steers (n = 140) were blocked by initial BW (432 ± 25.5 kg), stratified within blocks by intramuscular fat (3.6% ± 0.30%) determined by ultrasonography, and assigned to treatments (5 steers/pen, 7 pens/treatment). Treatments included 1) no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
4
6
1
Order By: Relevance
“…Cattle in the present study had plasma ascorbate values that exceed the normal range (2.4 to 4.7 mg/L) reported by Smith et al (2009), indicating excellent VC status of cattle in the present study. Plasma ascorbate values reported in the current study are similar to those reported by reported by Knight et al (1941) and Pogge and Hansen (2013a); however, in these studies, no decrease in plasma ascorbate was observed. The lack of a decrease in ascorbate concentration in response to treatment may be related to the age of the cattle used in the respective studies, 3-yr-old cows by Knight et al (1941) and Pogge and Hansen (2013a) compared to calf-fed steers (8 mo of age) used in the present study and by Pogge and Hansen (2013b).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Cattle in the present study had plasma ascorbate values that exceed the normal range (2.4 to 4.7 mg/L) reported by Smith et al (2009), indicating excellent VC status of cattle in the present study. Plasma ascorbate values reported in the current study are similar to those reported by reported by Knight et al (1941) and Pogge and Hansen (2013a); however, in these studies, no decrease in plasma ascorbate was observed. The lack of a decrease in ascorbate concentration in response to treatment may be related to the age of the cattle used in the respective studies, 3-yr-old cows by Knight et al (1941) and Pogge and Hansen (2013a) compared to calf-fed steers (8 mo of age) used in the present study and by Pogge and Hansen (2013b).…”
Section: Discussionsupporting
confidence: 90%
“…Plasma ascorbate values reported in the current study are similar to those reported by reported by Knight et al (1941) and Pogge and Hansen (2013a); however, in these studies, no decrease in plasma ascorbate was observed. The lack of a decrease in ascorbate concentration in response to treatment may be related to the age of the cattle used in the respective studies, 3-yr-old cows by Knight et al (1941) and Pogge and Hansen (2013a) compared to calf-fed steers (8 mo of age) used in the present study and by Pogge and Hansen (2013b). The differing response in plasma ascorbate during the finishing period may indicate that calf-fed cattle have a greater requirement for VC compared to yearling steers.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations